2011
DOI: 10.1111/j.1365-2656.2011.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual condition and habitat quality on natal dispersal behaviour in a small rodent

Abstract: 5Norsk Polarinstitutt, Seabird ecology and management, Polarmiljøsenteret, 9296 Tromsø, Norway Summary 1. Individuals should benefit from settling in high-quality habitats, but dispersers born under favourable conditions have a better physical condition and should therefore be more successful at settling in high-quality habitats. 2. We tested these predictions with root voles (Microtus oeconomus) by a manipulation of individual condition through litter-size enlargement and reduction during lactation combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 63 publications
1
46
1
Order By: Relevance
“…In fact, several studies of mammals and birds have shown that parents cannot fully compensate for the increased energetic requirement of an enlarged brood (Monaghan, 2008; Rémy et al., 2011). Bonelli’s eagles usually lay one or two eggs (Real, 1991), so females have to face a trade‐off between forming one or two eggs at the time of egg formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, several studies of mammals and birds have shown that parents cannot fully compensate for the increased energetic requirement of an enlarged brood (Monaghan, 2008; Rémy et al., 2011). Bonelli’s eagles usually lay one or two eggs (Real, 1991), so females have to face a trade‐off between forming one or two eggs at the time of egg formation.…”
Section: Discussionmentioning
confidence: 99%
“…An individual’s internal state can provide information on the fitness potential of its environment, thereby affecting its decision to stay or leave its natal area (Clobert et al., 2012). In other words, the costs and benefits of natal dispersal are influenced by the internal state of individuals and by environmental conditions experienced both in the natal area and in future breeding sites (Acker et al., 2018; Bonte et al., 2012; Bowler & Benton, 2005; Clobert et al., 2009; del Mar Delgado, Penteriani, Revilla, & Nams, 2010; Rémy, Le Galliard, Gundersen, Steen, & Andreassen, 2011). Thus, both modeling and empirical studies indicate that natal dispersal behavior often represents a plastic‐, phenotype‐, and condition‐dependent strategy (Bonte et al., 2012; Clobert et al., 2012; Rémy et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance can be measured as an individual's reluctance to cross a boundary, the physical cost of the movement, or increased mortality risk (Zeller et al 2012). Resistance can result from the perceived level of risk to entering the matrix (Fahrig 2007), the quality of the habitat being dispersed from (Roe et al 2009), or the social pressures pushing individuals to disperse (Remy et al 2011). By quantifying the resistance of landcover types in the matrix, researchers can predict the direction of dispersal in the landscape and estimate overall habitat connectivity (Ricketts 2001).…”
Section: Introductionmentioning
confidence: 99%